The Pacific War in The Chilean School Space: Teaching History, Discourses and Ritual Practices, 1879-1929 - Cid, Gabriel; Fernández, Camilo; Hernández, Cristóbal (Revista de Historia Social y de las Mentalidades, 2023)
This article examines the role played by Chilean schools in the reproduction of the imaginary of the War of the Pacific in the decades following the conflict. Examining this process from the perspective of the cultural history of the war, the research studies the nationalist uses of the teaching of the history of the conflict in schools, the circulation of patriotic narratives in the context of the school press and teaching activity and, finally, the part that commemorations associated with the war played in the socialization of patriotic discourse and practices in school audiences.